Efeitos do tratamento da má oclusão de classe II por deficiência mandibular após uso do propulsor mandibular de Herbst e aparelho corretivo fixo - Comparin, Rodrigo (2013)
Objective: To investigate the dentoskeletal and soft tissue effects treatment of malocclusion Class II, Division 1, for mandibular deficiency, after the use of propellant Herbst and mandibular orthodontic appliance Straight Wire. Material: the sample, retrospective, consisted of radiographs of 24 young patients, Brazilian, female (five) and male (nineteen) , initial mean age 13.7 , feoderma ethnicity (four) and leucoderma (twenty) selected from a total of 1625 patients treated in the Specialization Course in Orthodontics PROFIS, Bauru - Sao Paulo, Brazil. Methods: radiographs were used in lateral view before the start of orthodontic treatment (T1), after treatment with mandibular propellant Herbst (T2), and after completion of orthodontic treatment with braces Straight Wire (T3). The mean time of treatment was 2.2 years (T1-T3). Results: of the 36 variables studied, only two variables (Pog-NB and inclination of the occlusal plane) showed systematic error. The random errors were very low and acceptable. The sample showed normal distribution. Two quantities used to express the change of the sagittal position of the maxilla (SNA and A- Nperp), not fluctuated significantly, only the distance Co A increased in T3 stage anteriorly. The quantities used to express the change in the sagittal position of the mandible (SNB, P-Nperp and Co-Gn) increased between stages T1 and T2, however, the T3 stage there was a return to the original position for the SNB and variable P-Nperp (Stage T1 similar to Stage T3), except the variable Co-Gn, which remained stable between T2 and T3 stages. No change in growth pattern, only an increase in lower anterior facial height (ANS-Me), between T1-T2 stages, remaining stable between T2 and T3 stages. The upper incisors decreased buccal tipping (except 1.PP variable) and the protrusion between the T1 and T2 stages and remained stable in T3 stage. The lower incisors inclined labially and protruded. In the vertical direction, there was no change in position of molars and incisors intruded. The overjet, overbite, molar and canine relationship, decreased in the three stages of development, and, for the inclination of the occlusal plane, there was a decrease between T1 and T2 stage, remaining stable in T3 stage. To compare the soft tissue components, the profile convexity decreased (NB-H and H-Nose), the upper lip protruiu between T1 and T2 phases and was stable between T2 and T3 phases. There was an increase in airway (NFA- NFP and Bfa-Bfp) between T1 and T2 stage. Conclusion: When assessing the overall treatment time is concluded that major changes were dentoalveolar and soft tissue. Treatment with the Herbst mandibular propulsion machinery followed by orthodontic appliance Straight Wire resulted in occlusal and aesthetic benefits for patients, young adults, presenting malocclusion Class II, Division 1, for mandibular retrusion